MASYARAKAT ISLAM IDEAL DALAM KONSEPSI FILSAFAT PENDIDIKAN ISLAM - Muqoyyidin, Andik Wahyun (Pascasarjana UIN ANTASARI Banjarmasin, 2014)
The essence of society is an integral part of the discussion of the philosophy of Islamic education. Fazlur Rahman even conclude that the primary purpose of the Qurâan is to enforce a social order thatâs fair and ideal. As a community order which emphasizes tolerance, democracy and civilized, civil society to contribute positively to the needs of Muslims today. For the basic concept of philosophy of Islamic education should be placed in the context of civil society supra-system of education in which it will be applied. Therefore reconstruction of Islamic educational philosophy into something very urgent and relevant to todayâs problems of Islamic education.